Environmental and Biosafety Research Ethics Committees: Guidelines and Principles for Ethics Reviewers in the South African Context - Van Rooyen, Maricel (Stellenbosch : Stellenbosch University, 2021)
Thesis (MPhil)--Stellenbosch University, 2021.